A biblioteca escolar na era da internet: uma análise na Biblioteca do CCBEU - OLIVEIRA, Ingrid Amanda Barros (2019)
The present work seeks to show how the Internet is an important mediation tool within a school library, because in an era in which all are connected it is important to use this information medium to attract the user and stimulate their creativity. The role of the librarian is also discussed, since the librarian needs to have an innovative vision so that he can use this method within the school library and must always be updating since, as a manager, he must assume this role by knowing the profile of the users so that he can make the correct connection between mediation of information and its user within the school library. The applied methodology was based on books, theses, databases, dissertations, etc. and two questionnaires applied within the CCBEU library that can show how significant the internet is inside a school library, it also indicates the attractive methods within it. As a result of the discussion, users' preferences in activities involving the internet were observed and showed that everyone preferred these actions in the library, since they can use cell phones, tablets among others when they are not using these tools are done other activities that also stimulate the user to always seek and mediate information. It was possible to verify that the environment of this school library has changed or adapted to the new technologies, causing the librarian to develop other activities in other spaces that involve the internet.